Who decides? : states as laboratories of constitutional experimentation - Sutton, Jeffrey S. (Jeffrey Stuart), 1960- (New York, NY : Oxford University Press, 2021)
In 'Who Decides', Jeffrey S. Sutton makes the case that American Constitutional Law should account for the role of the state courts and state constitutions, together with the federal courts and the federal constitution, in establishing the structure of the 51 American governments. An underappreciation of state constitutional law has hurt state and federal law and has undermined the appropriate balance between state and federal courts in protecting liberty. Sutton aims to correct this imbalance and to illustrate the virtues of federalism for all Americans and for all pressing matters of government.
Also issued in print: 2021.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 9, 2021).
Keywords: Constitutional law -- United States -- States; Constitutional amendments -- United States -- States; Constitutional history -- United States -- States; Federal government -- United States